2015
DOI: 10.1038/cdd.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

The BH3-only protein BIM contributes to late-stage involution in the mouse mammary gland

Abstract: After cessation of lactation, involution of the mouse mammary gland proceeds in two distinct phases, a reversible and an irreversible one, which leads to the death and removal of alveolar cells. Cell death is preceded by the loss of STAT5 activity, which abrogates cell differentiation and gain of STAT3 activity. Despite early observations implicating BCL2 (B cell lymphoma 2) family proteins in this process, recent evidence suggests that STAT3-controlled cathepsin activity is most critical for cell death at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 63 publications
2
25
1
Order By: Relevance
“…Among known factors that control canonical mitochondrion-associated apoptosis, we identified the genes encoding the BH3-only proteins BMF and BIM (Bcl2l11) to be targets of JAK1 signaling. The results of analysis of involuting mammary glands of single-knockout mice confirm the findings presented in a recent report that showed that both proapoptotic proteins contribute to the initiation of apoptosis (58). More importantly, using a BMF/BIM-double-knockout transplant model, we now provide clear evidence that both of these JAK1 targets act synergistically in an epithelium-specific manner.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Among known factors that control canonical mitochondrion-associated apoptosis, we identified the genes encoding the BH3-only proteins BMF and BIM (Bcl2l11) to be targets of JAK1 signaling. The results of analysis of involuting mammary glands of single-knockout mice confirm the findings presented in a recent report that showed that both proapoptotic proteins contribute to the initiation of apoptosis (58). More importantly, using a BMF/BIM-double-knockout transplant model, we now provide clear evidence that both of these JAK1 targets act synergistically in an epithelium-specific manner.…”
Section: Discussionsupporting
confidence: 77%
“…According to the ChIP-Seq and ChIP/qRT-PCR results, STAT3 is bound to the chromatin in proximity to the Bmf and Bim loci, and its association with GAS sequences near transcriptional start sites was increased during involution. This finding suggests that STAT3 might be directly involved in the transcription of these genes, and it is therefore puzzling that STAT3-knockout mice did not show the same deregulated expression in Bmf and Bim that was observed in the JAK1-knockout mice (58). One possible explanation is that other transcription factors whose expression levels are controlled by JAK1 (e.g., Runx1) also contribute to the expression of Bmf and Bim.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Additionally, increased lymphadenopathy, higher serum Ig levels, and a higher incidence of glomerulonephritis and malignant disease, leading to premature lethality, were observed when compared with BIM mutant mice (Labi et al 2014;Woess et al 2015). BMF also supports BIM in promoting mammary epithelial cell death during organ morphogenesis Schmelzle et al 2007) and the late stage of involution after the cessation of lactation, a classic example of developmental apoptosis (Sakamoto et al 2016;Schuler et al 2016).…”
mentioning
confidence: 99%
“…As such it connects the extrinsic and intrinsic apoptosis signaling pathways in certain cell types that rely on efficient neutralization of XIAP to generate above-threshold caspase activity upon death receptor (DR) ligation (Jost Bouillet et al 1999Bouillet et al , 2002Hildeman et al 2002;Enders et al 2003;Pellegrini et al 2003;Villunger et al 2003b;Fischer et al 2007;Mailleux et al 2007;Schuler et al 2016 Bmf Normal embryonic development; lymphocytes and MEFs partially protected from glucocorticoid or histone deacetylase inhibition (HDACi)-induced apoptosis; mild Bcell hyperplasia; potential overlap with BIM in mammary gland involution Labi et al 2008;Hubner et al 2010;Sakamoto et al 2016;Schuler et al 2016 Bid Normal embryonic development; hepatocytes resist FasLinduced and TNF-induced hepatitis; delayed apoptosis upon FasL or TNF-α treatment in MEFs; pancreatic β cells resist death receptor (DR) killing; reduced response to the DNAdamaging agents (controversial); neurons more protected from ischemic cell death (controversial) Yin et al 1999;Plesnila et al 2001;Sax et al 2002;Kamer et al 2005;Zinkel et al 2005;Kaufmann et al 2007Kaufmann et al , 2009McKenzie et al 2008;Engel et al 2010 Bad Normal embryonic development; minor protection from apoptotic stimuli; modest reduction in B-cell proliferation in response to mitogens; decreased production of IgG upon immunization; prolonged platelet life span; reduced sensitivity to TNF-induced hepatitis (controversial); impaired glucose stimulated insulin secretion and glucokinase activity Danial et al 2003;Ranger et al 2003;Kelly et al 2010;Yan et al 2013;Ottina et al 2015 Puma Normal embryonic development; hematopoietic and nonhematopoietic cell types highly resistant to genotoxic stress and γ irradiation as well as growth factor deprivation; high-fat-diet-fed as well as chow diet-fed mice show decreased food intake and ambulatory capacity Jeffers et al 20...…”
mentioning
confidence: 99%